Struktur Fisik dan Batin Puisi Audio Visual Youtube sebagai Bahan Ajar Sastra Digital - Liza Septa Wilyanti; Sovia Wulandari (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
As one of the literary genres, poetry has also begun to experience new forms of adaptation in the world of digital literature. One of these forms is audio-visual literature. Audio-visual poetry uses media such as YouTube as its publication medium. This can be seen in the emergence of youtube accounts that consistently produce audio-visual poems. The audio-visual poems on several accounts have even been watched by millions of viewers. This study aims to determine the physical and mental structure of audio-visual poems on these accounts and to describe the appearance of audio-visual poetry on Youtube digital media. This research is included in descriptive qualitative research. This study analyzes 12 Youtube audio-visual poems that are considered the most popular. The audio-visual poems were taken from 6 different Youtube channels, namely the poems â€œAjari Aku untuk Melepaskanmuâ€ and â€œRindu untuk Ayahâ€ from Pena Safa's Youtube account. Poems â€œKetika Kukira Aku Istimewaâ€ and â€œHarapan yang Tumbuh, Hati Yang Patahâ€from the Fictionalism Youtube account. The poems â€œCurahan Hati Seorang Perokokâ€ and â€œRokok dan Kamu 2â€ from the Normantin TV Youtube account. Poems â€œCintaâ€ and â€œRasa dan Perasaanâ€ from Ega Nugraha's Youtube account. The poems â€œSakitnya Aku Mencintaimuâ€ and â€œIngin Menangis Sebentar Sajaâ€ from the Youtube account Jejak Sulas. The poems "â€œMenangislahâ€ and â€œDesember dan Lukanyaâ€Some poems such as "When I Think I'm Special" and â€œCintaâ€ are not the work of the Youtube account owner, but are the work of other people who are read out. The poem â€œKetika Kukira Aku Istimewaâ€ is the work of Fiersa Bersari and the poem â€œCintaâ€ is a famous poem by Khalil Gibran. The aspects analyzed are the physical and mental structure as well as the audio-visual form of poetry on the digital media Youtube. Most of Youtube's audio-visual poems that have a high number of viewers do not yet have a complete physical and mental structure of poetry. Audio Visual forms on Youtube audio visual poetry are very free and depend on the creativity of the owner.